Mediating Effect of Perceived Organizational Support Between Job Satisfaction and Job Stress Among Operation Supervisors in Private Organizations - Advincula, Joemar (Journal of Interdisciplinary Perspectives, 2025)
This study examined the impact of perceived organizational support and job stress on job satisfaction among operational supervisors and whether perceived organizational support mediates the relationship between job stress and job satisfaction. It utilized a quantitative research design, specifically mediation analysis, to address its objectives. The study was conducted in Calamba City and employed a stratified sampling method to gather data from 172 operation supervisors in private organizations in Calamba City. The study used three adopted survey questionnaires: the Perceived Organizational Support Scale, the Global Job Scale, and the Brief Job Stress Questionnaire (BJSQ). In addition, using regression analysis, it was found that job stress predicted perceived organizational support with a computed R-squared of 0.130; perceived organizational support predicted job satisfaction with an R-squared of 0.099; and job stress predicted job satisfaction, given a computed R-squared of 0.074. Moreover, to determine whether perceived organizational support acted as a mediator between job stress and job satisfaction, the Sobel test was employed. Sobel’s test revealed that perceived organizational support partially mediated the relationship between job stress and job satisfaction, with test statistics of 1.59 and a probability value of 0.039. In conclusion, perceived organizational support continues to affect job satisfaction, regardless of the presence of job stress. Given these results, Program C.A.R.E. was proposed to enhance the perceived organizational support, job stress, and job satisfaction of operational supervisors.